Halal Awareness on Self Declaire Halal Certification Program - Baidhowi, Muhammad Mujib; Triwibowo, Ananto (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The development of micro and small businesses in Indonesia is always increasing, so the role of the government is needed to supervise the products produced, both starting from the raw materials used, the manufacturing process to being ready to be distributed to consumers. Halal awareness or halal awareness is a basic thing and must be owned by business actors so that the products traded have guarantees in terms of process and law in accordance with the provisions of Islamic sharia. So that the implementation of Halal Awareness is considered important in the ongoing halal certification program. This study uses a qualitative descriptive method using primary and secondary data which is then analyzed using several processes, namely, First, data reduction. Second, the presentation of data, after the data reduction process, the data is presented in the form of a description. And third, draw conclusions. The results obtained show that halal awareness which includes the indicators of Halal Syar'i Awareness (Zattiyah), Halal Awareness Hygienic, Halal Safe Awareness (Security) and Halal Quality has a very important role so that business actors consciously understand how to apply halal to their products, and this is in line with the government's role in the ongoing self-declaration program.